A novel all-composite blast-resistant door structure with hierarchical stiffeners. (15th July 2016) - Meng, Fanmao; Zhang, Bei; Zhao, Zheng; Xu, Ying; Fan, Hualin; Jin, Fengnian
Abstract: To develop light-weight blast-resistant door structures, sheet molding compound (SMC) material reinforced by carbon fiber reinforced plastic (CFRP) has been applied to make all-composite protective panels by adopting the method of one-step forming in mold filling and hot-molding compression. With skins, frames, stiffeners and sub-stiffeners, the door panel has hierarchical stiffened structure, making the door strong enough but much lighter. The CFRP reinforced SMC panel is four times stronger in extension and twice stronger in flexure than the SMC panel. The all-composite blast-resistant door structure can resist blast wave with peak pressure over 0.45 MPa, companying with stiffener fractures, frame cracks and skin cracks. CFRC reinforced SMC material effectively restricts the stiffener fracture, reduces the crack width and decreases the flexure of the door structure. All these composite door structures have dominant-elastic-response under explosion and restore their initial configuration after explosion.